Microsoft SharePoint 2010 administrator's pocket consultant - Curry, Ben (Microsoft Press, 2010)
"Your pocket-sized, fast-answers guide to administering SharePoint 2010 features quick-reference tables, lists, and instructions for concise, accurate answers on the spot"--Resource description page.
Title from title screen. - Includes index
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Intranets; Serveurs Web; intranets; COMPUTERS; Networking; Intranets & Extranets; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications